Nursing interventions in a newly established community health nursing system: A cross sectional survey - Raimund M. Kovacevic; Doris A. Behrens; Walter Hyll (Elsevier, 2024)
Background: Community health nursing was introduced in Austria in 2022. Information about nurses' activities, their alignment with established public health frameworks, and their relationship to existing care services is crucial for understanding the role's implementation and potential impact. Objective: This study examines the activities of the first cohort of Austrian Community Health Nurses, focusing on their alignment with the Public Health Intervention Wheel and the Nursing Intervention Classification. An important aspect comes from the question, whether these new services complement or substitute existing direct care services. In this process, we also address heterogeneity across urbanization levels. Design: Cross-sectional survey. Setting(s): An online survey (April to June 2023) among Community Health Nurses captured their perception of activity frequencies based on the Public Health Intervention Wheel and Nursing Intervention Classification. Participants: 130 nurses (59 %, N = 220) answered >6 (out of 33) questions, 98 nurses (45 %, N = 220) provided all required information. Methods: The analysis used descriptive statistics, statistical tests, and hierarchical cluster analysis, employing Excel®, Stata® and R. Results: Austrian Community Health Nurses implement many principles of the Public Health Intervention Wheel, with a focus on counselling, consultation, and health teaching. Direct care interventions (according the Nursing Intervention Classification) are rarely performed. Findings indicate that community health nurses complement rather than substitute existing direct care and home nursing services. However, unlike international practices, activities are primarily at the individual level, with limited engagement at community and systems levels. Conclusions: Community health nursing in Austria demonstrates a public health focus and therefore complements existing care services. However, it focuses primarily at the individual level, which differs from international norms where activities span individual, community, and systems levels. Tweetable abstract: First Austrian Community Health Nurses implement public health intervention principles mainly on individual level.